Malaysian food culture as a communal identity marker in Shih-Li Kow’s The Sum of Our Follies - Wan Putri Nurlisa Jaafar,; Melissa Shamini Perry,; Nor Fariza Mohd Nor,; Ravichandran Vengadasamy,; Pauline Pooi Yin Leong,; Loo, Hong Chuang (Penerbit Universiti Kebangsaan Malaysia, 2022)
Food is deeply rooted in cultural traditions and has been a ubiquitous and prominent element in cultural productions and narratives of cultures around the world. In literature, food is often employed literally and metaphorically to evoke the senses or communicate meaning about the identity, culture, or emotions of people. This article examines the connection between food and cultural identity in multicultural Malaysia as represented in the novel, The Sum of Our Follies by Malaysian author, Shih-Li Kow. It aims to identify how food is utilized in the novel to define a communal cultural identity for the characters in a fictional, small town of Lubok Sayong, Malaysia. Textual analysis of food references in the novel is employed to interpret the connection between food and cultural identity and draw parallels between the author-defined social reality in the novel and the Malaysian context. Anderson’s (2006) theory of the Imagined Community is applied to understanding communal identity as constructed through food and food spaces. The analysis revealed that food and food spaces are used as an indicator of a community’s geographical and physical environment, peer network, ethnicity, nationality and social class. Shih-Li Kow’s construction of social reality in this novel shed lights on the significant role of food culture as an identity maker for communities in Malaysia. The novel also captures the complexity of the Malaysian urban and small town sociocultural and socioeconomic divide through the lens of food culture.